2013
DOI: 10.1111/pim.12009
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic differences between the EG95‐related proteins from Echinococcus granulosus G1 and G6 genotypes: implications for vaccination

Abstract: Cystic echinococcosis caused by Echinococcus granulosus remains an important and neglected issue in public health. The study of the likely efficacy of the currently available EG95 vaccine against other genotypes of the parasite is important to improve the vaccine as a potential tool to be used in control programmes. The recombinant vaccine EG95-1G1 was developed based on the G1 genotype of E. granulosus. Characterization of the eg95 gene family in the G6 genotype by genomic DNA cloning previously produced the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 36 publications
1
26
0
Order By: Relevance
“…The G6 genotype displays features that are important for cystic echinococcosis diagnosis and control such as sequence variability in the diagnostic antigen B and the vaccine EG95 antigen . Also, differences in anti‐EG95 antibody response to infection between the G1 and G6 genotypes have been described . Echinococcus equinus (G4 genotype) has not been identified in South America yet, since the cystic echinococcosis cases found in horses lack genotype determination .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The G6 genotype displays features that are important for cystic echinococcosis diagnosis and control such as sequence variability in the diagnostic antigen B and the vaccine EG95 antigen . Also, differences in anti‐EG95 antibody response to infection between the G1 and G6 genotypes have been described . Echinococcus equinus (G4 genotype) has not been identified in South America yet, since the cystic echinococcosis cases found in horses lack genotype determination .…”
Section: Resultsmentioning
confidence: 99%
“…Also, E. canadensis (G6 genotype) plays a significant role in South American human cystic echinococcosis. Taking into account the molecular epidemiological situation, it is relevant to evaluate the pathogenicity, diagnosis performance and response to chemotherapy of the G6 genotype since antigenic differences between the EG95‐related proteins from the G1 and G6 genotypes were observed . Additionally, for an accurate determination of the public health relevance of E. canadensis (G7 genotype) in South America, a molecular epidemiological survey should be carried out in those regions where swine breeding is concentrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The currently most promising vaccine candidate EG95-1(G1) [44] differs also from its homologue in the E. canadensis (G6) by few AA variations (5 AA substitutions), but these substitutions result in conformational changes, which lead to a distinct difference in antigenicity between EG95-1G1 and EG95-1G6 [25], [26]. Indeed, antibodies from sheep vaccinated with EG95-1G1 did not react with EG95-1G6 antigen from E. canadensis (G6) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Variation neutrality was challenged for EG95 genes [22] and theoretically calculated data indicated a genetic polymorphism of the EG95 antigen-coding genes among different genetically characterized strains of E. granulosus [23]. Rojas et al [25], [26] showed that this variability affects the antigenicity of EG95 antigen, by demonstrating that recombinant protein EG95-1G6 ( E. canadensis (G6)) was not recognized by antibodies raised by sheep vaccinated with EG95-1G1. Genetic polymorphism in diagnostic/vaccine candidates was also reported for other parasites including protozoa (e.g.…”
Section: Introductionmentioning
confidence: 99%